A novel approach for craniofacial symmetry evaluation: Using the midsagittal Reference line drawn from “Crista Gali” with NHP technique - Ordobazari, Morteza; Naqavi Al-Hosseini, Ali Akbar; Zafarmand, Abdol Hamid (Novelty in Biomedicine, 2013)
Please cite this article as: Ordobazari M, Naqavi Al-Hosseini AA, Zafarmand H. A novel approach for craniofacial symmetry evaluation: Using the midsagittal Reference line drawn from “Crista Gali” with NHP technique. Novel Biomed 2013;1(2):48-53. Background and objective: The purpose of this study was the determination of midsagittal reference line (MSL) for craniofacial asymmetry assessment by drawing a line from Crista gali parallel to the true vertical line in PA cephalometry, using Natural Head Position (NHP) technique. Method and Materials: 60 Iranian subjects within the age range of 9-13 years old were selected for this prospective study. Patients referred for orthodontic treatment and ghad no supernumerary or missing teeth, no skeletal anomaly, or any history of orthodontic and jaw surgery with normal occlusion. Posteroanterior cephalometric radiographs (PA Ceph) were taken of all subjects with NHP technique. The midsagittal line was also traced parallel to the hanging chain from Crista gali. True horizontal line (THL) and true vertical line (TVL) were also traced from Crista gali (Cg). Using Cartesian system based upon Cg point (0 0), the craniofacial symmetry was assessed with linear, angular and proportional measurements in PA cephalogam, related to TVL and THL lines, for 10 bilateral (R&L) anatomical landmarks. The mean differences of the above measurements in left and right sides were analyzed by T- test. Results: The proportional ratios for all left and right measurements were not statistically significant. This was true for both vertical and horizontal distances. The significant level for MSL drawn from Cg as referred to ANS (0±0.255) and Me points (0.007±0.527) was 0.002 and 0.004, respectively. Conclusion: In posteroanterior cephalometry radiographs taken with NHP method, the MSL drawn from Crista gali is reproducible and reliable up to 96% of the times for facial symmetry diagnosis.